Critical Study on Arabic Learning by Non-Arabic Teachers and Employees Using Peer Learning in Assalaam Islamic Modern Boarding School - Pertapa Sari (Ittishal Educational Research Journal, 2020)
Speaking using Arabic and English has become mandatory in Assalaam Islamic Modern Boarding School. The Arabic and English must be used in the daily activities around the boarding school. Therefore, all employees, both teachers and employees, are competing to learn these two foreign languages; Arabic and English. One method used by the employees and also teachers to learn Arabic in the Boarding school is by having a kind of course held in each unit or division. Teachers, especially non-Arabic teachers are also curious in learning Arabic. Meanwhile, employees who are non-Arabic based education also curious to learn Arabic. Those non-Arabic teachers and employees conduct the Arabic learning by taking around two hours course per week held in the middle of the break time. The tutor for the non-arabic teachers of course the Arabic teacher, means the tutor is their own friend. And the tutor for the employees is an arabic teacher also. And we call it peer learning which is using their own friend to be the tutor. Within one year academic 2017/2018, the Arabic course is taken and it gives a lot motivation to the non-Arabic teachers and also the employees. Peer learninng method used seemed to be the correct method in holding a course for the teachers and employees. And the study about it shows that by using this method, the Arabic can be easier to learn by non-Arabic teachers and employees.